Kajian Neraca Kesesuaian Pemanfaatan Ruang Dalam Membangun System Informasi Tata Ruang Wilayah Kabupaten - Muspriyono, Agung; Ayub Muktiono; kasman (Journal of Urban and Regional Development Studies, 2023)
Balance Sheet Study of the Suitability of Space Utilization in Building a Regency Spatial Planning Information System, harmony and spatial planning rules, carrying capacity and capacity, as well as proper and adequate infrastructure, causing the area to become uninhabitable. In the context of developing spatial management, it is necessary to prepare a spatial planning register to see whether the implementation of spatial planning is in accordance with the spatial planning plan and to see the availability of remaining space allocations that can still be used which are classified based on villages/sub-districts, sub-districts, development areas and spatial patterns. The results of the suitability analysis of space use show that in Bekasi Regency there are land uses that are suitable, inappropriate and incompatible (not yet tangible) with land use in the 2011-2031 spatial pattern plan. The area of land use that is in accordance with the spatial pattern designation is 55,203.55 Ha, land use that is not in accordance with the spatial pattern designation is 13,530.51 Ha, and land use that is not appropriate (not yet tangible) is 57,803.97 Ha